THE EFFECT OF FINANCIAL RATIO ON VALUE COMPANIES WITH FINANCIAL DISTRESS AS INTERVENING VARIABLES IN THE COMPANY MANUFACTURE - Anthonius Yanto Gebang; Yusrizal Purba (UPMI Management, 2022)
Globalization that has occurred throughout the world has significantly impacted various aspects of the life of the world community. This study aimed to determine the direct effect of liquidity, solvency, profitability, and financial distress on firm value partially and simultaneously, as the indirect effect of liquidity, solvency, and profitability on firm value through financial distress as an intervening variable. This study uses a quantitative approach. In a sample of 28 companies, this study uses SPSS 22. The results of testing the liquidity effect on the firm value obtained t count 2.424 > t table 2.093 and a significance of 0.048 <α = 0.05. The results of testing the effect of solvency on the firm value obtained t count 2.558 > t table 2.093 and a significance of 0.013 <α = 0.05. The results of testing the liquidity effect on the firm value obtained t count 0.098 > t table 2.093 and a significance of 0.922 <α = 0.05. The results of testing the liquidity effect on the firm value obtained t count 2.152 > t table 2.093 and a significance of 0.019 <α = 0.05. Sobel test results show that financial distress cannot mediate the indirect effect of liquidity, solvency, and profitability on firm value. The regression coefficient for the direct effect of liquidity on firm value is 0.739. Meanwhile, the indirect effect of liquidity through financial distress as an intervening variable is -0.03293. JEL Classification: M10, M21, M41